The relationship between AGR2 levels and intestinal barrier function in high-fat diet animal models: High-fat diet regulates intestinal barrier through AGR2 - Kang, Facai; Zhao, Shuhong; Ren, Huimin; Yang, Jing; Chen, Sizhen; Kou, Qi; Sun, Jing (Cellular and Molecular Biology, 2023)
This study aimed to observe the effect of anterior gradient protein 2 (AGR2) levels on intestinal barrier function in HFD animal models. For this purpose, thirty healthy male clean-grade C57BL/6 mice were randomly separated into a normal control group and a high-fat group. The normal control group was fed a normal diet, while the high-fat group was fed an HFD for a total of 8 weeks. It collected body weight changes before and after modeling of two groups of rats and serum samples and detected fasting blood glucose, total cholesterol, triglycerides, AGR2, and diamine oxidase (DAO) concentrations. It collected the expression levels of AGR2 in the colon of rats after modeling, evaluated the permeability of the colon and small intestine barrier by Ussing chamber and Evan’s blue (EB) methods, and analyzed the correlation between AGR2 levels and intestinal barrier function using Pearson correlation. Results showed that when the two groups of mice were fed for 8 weeks, their body weight, fasting blood glucose, total cholesterol, and triglycerides all met the characteristics of an HFD mouse model, and the model was successfully established. When the two groups of mice were fed for 8 weeks, the serum AGR2 concentration, relative expression of AGR2 in colon tissue, Gt, and EB content of the high-fat group mice were higher than those of the normal control group, and the difference was significant (P<0.05); Meanwhile, the serum DAO concentration and Isc of the high-fat group mice were lower than those of the normal control group, with statistically significant differences (P<0.05); The relative expression levels of serum AFR2 and colon AGR2 were negatively correlated with Isc (r=-0.503, -0.623, P<0.05), and positively correlated with Gt (r=0.461, 0.560, P<0.05). There was a homogeneous distribution characteristic between the relative expression levels of serum AFR2 and serum DAO, colon AGR2, and Isc variables. It was concluded that HFD could upregulate the expression of AGR2 in mice, downregulate the level of DAO, and damage the intestinal barrier function of mice. Both serum AGR2 concentration and colonic AGR2 relative expression can participate in the regulation of colonic intestinal barrier function and can serve as potential indicators for evaluating intestinal barrier damage.